A review of the gekkotan lizards of Bénin, with the description of a new species of Hemidactylus (Squamata: Gekkonidae) - Bauer, Aaron M.; Tchibozo, Sévérin; Pauwels, Olivier S. G.; Lenglet, Georges (Zootaxa, 2006)
The gecko fauna of Bénin is extremely poorly known, with only two species having previously been mentioned in the literature on the basis of voucher specimens. We provide evidence for the occurrence of seven additional species, bringing the national total to nine confirmed species. Another five species are known from localities to both the east and west of Bénin and almost certainly are part of the national fauna. One of the species confirmed for Bénin is a new species of Hemidactylus. This new form is distinguished by its 14–16 dorsal tubercle rows, enlarged median subcaudal scales, atuberculate tail dorsum, 38 precloacal-femoral pores, and 6–7 (usually 7) divided scansors beneath digit four of both the manus and pes. We also provide the first record of Lygodactylus conraui for Togo.